Abnormal Activation of Tryptophan-Kynurenine Pathway in Women With Polycystic Ovary Syndrome - Wang, Siyu; Mu, Liangshan; Zhang, Chunmei; Long, Xiaoyu; Zhang, Yurong; Li, Rong; Zhao, Yue; Qiao, Jie (Frontiers in Endocrinology, 2022)
Background Women with polycystic ovary syndrome (PCOS) suffer from dysfunctional metabolism and studies have reported increased levels of tryptophan in patients with PCOS. However, the changes of downstream metabolites in tryptophan catabolism pathways remain unclear. Methods This is a cross-sectional study that included 200 PCOS patients and 200 control women who were recruited from the Reproductive Medicine Center of Peking University Third Hospital from October 2017 to June 2019. The PCOS patients and the control group were further divided into subtypes of normal weight and overweight/obesity. Fasting blood samples from all subjects were collected on days 2 3 of a natural menstrual cycle or when amenorrhea for over 40 days with follicle diameter not exceeding 10 mm. The plasma levels of tryptophan metabolites were quantitatively determined by the liquid chromatograph mass spectrometer, including tryptophan, serotonin, kynurenine, kynurenic acid, 3-hydroxykynurenine, and quinolinic acid. Results The tryptophan-kynurenine pathway was dysregulated in women with PCOS, along with significantly elevated levels of tryptophan, serotonin, kynurenine, kynurenic acid, and quinolinic acid. Moreover, levels of tryptophan, kynurenine, and kynurenic acid were positively correlated with luteinizing hormone, anti-Müllerian hormone, fasting insulin, HOMA-IR. tryptophan, and kynurenine and quinolinic acid had an obvious association with C-reactive protein levels. Furthermore, logistic regression showed that tryptophan, serotonin, kynurenine, kynurenic acid and quinolinic acid were all associated significantly with the increased risk of PCOS with the adjustment for potential confounding factors. Additionally, tryptophan, kynurenine, and kynurenic acid had good diagnostic performances for PCOS, and their combination exhibited higher sensitivity and specificity to diagnostic efficiency, with the area under the ROC curve of 0.824 (95% CI 0.777-0.871), which was comparable to the endocrine indicators. Conclusion (s) The tryptophan-kynurenine pathway was abnormally activated in PCOS patients.